The Correlation between Knowledge Level of Young Girls and Breast Cancer Prevention in Class (X) Students at SMA Taman Siswa (TAMSIS) Pematang Siantar - Yulia Delfahedah (PT Inovasi Pratama Internasional, 2023)
Cancer breast is one reason main death consequence cancer in women. Cancer breast is malignancy the most second in women after cancer mouth uterus. Height number death consequence cancer breast caused sufferer cancer breast come to service health in the inoperable stage or advanced stage and not do BSE action so hard cured. Study this aim for knowledge teenager with prevention cancer breasts